Examining the expansion of Urban Heat Island effect in the Kolkata Metropolitan Area and its vicinity using multi-temporal MODIS satellite data. Issue 5 (1st March 2022) - Mandal, Jayatra; Patel, Priyank Pravin; Samanta, Sourav
Highlights: The temporal LST has increased 2.5 times higher in KMA than the surrounding area. Premonsoon was the warmest followed by monsoon, postmonsoon and winter periods. The urban heat island growth and urban growths were 44.65 sq. km and 28.74 sq. km. Highest urban heat island extent index noted in WSW direction while least in SSE. City's center and 20 km ring buffer was highly unhealthy. Abstract: This study examines the Urban Heat Island (UHI) phenomena in the Kolkata Metropolitan Area (KMA) region and its surrounding rural areas based on MODIS satellite data of the last two decades (2001-19). The temporal land surface temperature (LST) has increased in both the KMA and its neighborhood, with this rate of increase being 2.5 times higher in the KMA as compared to its surroundings. Seasonally, the pre-monsoon period was the warmest, with an average LST of 32.0 °C, followed by the monsoon (30.5 °C), post-monsoon (28.6 °C) and winter (25.0 °C) periods, respectively. Especially during the pre-monsoon, the ambient high air and LSTs extenuate the UHI scenario, causing much discomfort to residents. The human health comfort map identified that the city's center and a 20 km buffer around it contained stressful health conditions, with about 90% of the heat island situated within this zone. The total amount of UHI growth was 44.65 sq.km, with an urban expansion of 28.74 sq.km and the highest UHI extent index (UHIEI) was identified in the WSW direction, with it being least towards SSE. High-rise buildings and population density has increased rapidly with concomitant decline in greenery during the study period, and therefore the Normalized Difference Vegetation Index (NDVI) values are lower within the KMA but more enhanced in the surrounding rural areas. Spaces that enable quicker lowering of the LST are also more in areal extent in these surrounding rural areas. Practices of water roof and green roof wherever possible and planting of trees in available spaces within the city is urgently required to mitigate the UHI effect. This time series based study can guide future planning efforts towards decreasing the adverse effects of urbanization induced by heat islands and make possible an eco-friendly and sustainable urban development in this region.